The Relationship of Communication and Children's Age with Readiness for Menarche in Students of SMP Negeri 1 Enrekang - Kasim, Erna (Hasanuddin Medan, 2022)
The aim of the research was to determine the relationship between mother-child communication and child age with readiness to face first menstruation (menarche) in female students at SMP Negeri 1 Enrekang, Enrekang Regency. The research method used is an analytical approach using a cross sectional design. The population in this study was a total of 132 people. The sample studied consisted of 99 respondents, from March 23 to April 13 2015. Data was collected using a questionnaire and then analyzed using the Chi square statistical test with a significance level of ? < 0.05. The results of research on mother-child communication related to readiness to face the first menstruation (menarche) obtained a value of p = 0.000 < 0.05, and the child's age in relation to readiness to face the first menstruation (menarche) obtained a value of p = 0.004 < 0.05. Based on the research results, it was concluded that there is a relationship between mother-child communication and readiness to face the first menstruation (menarche), and there is a relationship between the child's age and readiness to face the first menstruation (menarche), suggestions for future researchers are to pay attention to several internal factors related to readiness to face the first menstruation (menarche), for example the level of knowledge of teenagers about the first menstruation (menarche), and also other factors so that teenagers are better prepared to face the first menstruation (menarche).